The chronic coronary syndrome—Heart failure roundabout: A multimodality imaging workflow approach - Lala, Radu I.; Mercea, Simona; Jipa, Radu A.; Puschita, Maria; Pop-Moldovan, Adina (Frontiers in Cardiovascular Medicine, 2022)
Heart failure is a complex syndrome of considerable burden with high mortality and hospitalizations rates. Approximately two thirds, of patients with heart failure have ischemic etiology therefore identifying relevant coronary artery disease is crucial. Moreover, patients with chronic coronary syndrome can first present with dyspnea and left ventricular dysfunction. If establishing diagnosis of HF and consequent management is clear enough, things don’t stand the same way when it comes to recommendations for etiology assessment. Ischemic heart disease is the most studied disease by cardiac multimodality imaging with excellent diagnostic performance. Based on this aspect, the high prevalence of coronary artery disease and worst outcome, Heart failure patients should undergo a diagnostic work-up by using these multimodality imaging techniques. The aim of this mini-review is to provide insights on multimodality imaging for diagnosing chronic coronary syndrome in patients with new onset of HF and propose a diagnostic work-up based on current international studies and guidelines.